Cuidado de enfermería al paciente con trauma, en el servicio de urgencias en una institución de tercer nivel, Medellín, 1998 (2000)
ABSTRACT: In this work, the characteristics of the nursing care which was provided to patients who were consulted for trauma in an emergency room in Medellin, Colombia, is described. The investigators used the recommendations about the importance of direct care to the patient by nursing professionals such as interdisciplinary work and the concept of inclusion of the patient and his family in his plan of care (such as fundamental elements to achieve adaptation of the disease process in an environment which is more comfortable, ethical and human, where optimal recuperation is obtained and with the least sequels possible). The frequency which care was fulfilled was analyzed, starting with the evaluation of the patient to detect problems to the directed activities to prevent complications which are considered fundamental in the inicial care. A lack of care was found due to circumstances explained as multi-causal which had to do with personal motivation, academic preparation, and institutional policies.